An Introduction to the Japonic Languages Grammatical Sketches of Japanese Dialects and Ryukyuan Languages - Shimoji, Michinori (Brill, 2022)
Japanese is definitely one of the best-known languages in typological literature. For example, typologists often assume that Japanese is a nominative-accusative language. However, it is often overlooked that Japanese, or more precisely, Tokyo Japanese, is just one of various local varieties of the Japonic language family (Japanese and Ryukyuan). In fact, the Japonic languages exhibit a surprising typological diversity. For example, some varieties display a split-intransitive as opposed to nominative-accusative system. The present volume is thus a unique attempt to explore the typological diversity of Japonic by providing a collection of grammatical sketches of various local varieties, four from Japanese dialects and five from Ryukyuan. Each grammatical sketch follows the same descriptive format, addressing a wide range of typological topics.